PELATIHAN PEMBUATAN WEBSITE DENGAN MENGGUNAKAN APLIKASI WIX - Virginia, Callista; Jeovanni Wong; Umar Muhdhor; Intan Sanu; Richie Jonathan Chaniago; Ery Hartati (Jurnal Pengabdian, 2025)
The development of technology and information requires students to be able to master the necessary skills. This training aims to improve students' digital literacy in facing rapid technological developments. Website creation is one of the skills from utilizing information and communication technology products. Wix was chosen as a website creation platform because it is drag-and-drop based, user-friendly, and does not require coding skills. This training introduces the basic concepts of website creation, utilization of Wix features, and practice in building a simple online store website. The methods used in this training include training methods and science and technology simulation methods, which combine theory and practice directly. This activity was attended by students and received a positive response. The results of the training showed an increase in students' abilities in utilizing information technology, both for academic and personal purposes. In addition, this training also encourages students' creativity and innovation in self-development in the digital era. Because of that, website development skills should be taught from an early age across various groups in order to prepare students to compete and thrive in the digital era.